2016
DOI: 10.1097/iop.0000000000000591
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Orbital Reconstruction in Patients with Prior Orbital Fracture Repair

Abstract: This study demonstrates that secondary orbital reconstruction can achieve excellent functional and cosmetic results with high patient satisfaction and minimal complications. Secondary reconstruction of previously repaired orbital fractures should be considered when clinically indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 21 publications
0
21
0
1
Order By: Relevance
“…The potential late cosmetic deformities include superior sulcus deformity, hypoglobus, and enophthalmus. 6,7 Surgeons predict the potential risk for functional and/or late cosmetic symptoms based on clinical and CT scan findings, knowing that not all BOFs require surgical treatment. 8 The cut-off points between surgical and nonsurgical treatment have been recommended at > 1.5 mL volume of herniation, 9 an orbital floor fracture > 1.0 cm, 2,10 or > 50% fractured orbital floor.…”
mentioning
confidence: 99%
“…The potential late cosmetic deformities include superior sulcus deformity, hypoglobus, and enophthalmus. 6,7 Surgeons predict the potential risk for functional and/or late cosmetic symptoms based on clinical and CT scan findings, knowing that not all BOFs require surgical treatment. 8 The cut-off points between surgical and nonsurgical treatment have been recommended at > 1.5 mL volume of herniation, 9 an orbital floor fracture > 1.0 cm, 2,10 or > 50% fractured orbital floor.…”
mentioning
confidence: 99%
“…Previous reports showed that 27.5% of the patients had residual enophthalmos and 20%–37% of patients had postoperative diplopia after surgery [1416]. The decision for secondary repair was based on clinical presentation correlated with radiographic findings, such as a malpositioned or absent orbital implant [6]. Secondary orbital reconstruction for unsatisfactory primary orbital repair can improve functional deficits and aesthetic results [6].…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate primary orbital repair causing functional defects and cosmetic deficits is a great challenge for those surgeons who decide to perform secondary reconstruction surgery. Scarring accompanying the primary incision and fibrosis in response to implanted orbital materials increase the risks of complications associated with secondary surgery [6]. Nevertheless, if secondary surgery is performed, it can substantially improve patients' quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that entrapment of extraocular muscle is an absolute indication for immediate surgical intervention. 1 It is also known that BOF can result in considerable aesthetic deformities, 2,3 hypoesthesia of the infraorbital nerve, 4 and chronic diplopia. 5 Early assessment of the significance of the fracture through clinical examination and imaging and an informed decision between surgical and observational treatments are crucial for an optimal result.…”
mentioning
confidence: 99%